Urgensi Pengaturan Pembatasan Transaksi Tunai di Indonesia - Al-Jufri, Andi Ikram Fadhil Mubarak; Amrain, Fitran; Tendean, Meyer (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2025)
Restrictions on cash transactions in Indonesia are a strategic policy aimed at strengthening financial system stability, improving payment efficiency, and preventing financial crimes such as money laundering and terrorist financing. This study employs a normative juridical method, analysing legal documents, banking regulations, and Islamic economics and finance literature. This study finds that rules related to cash transaction restrictions have been regulated through the Banking Law, Bank Indonesia Regulations, Financial Services Authority regulations, and the Law on the Prevention and Eradication of Money Laundering. From an Islamic economics and banking perspective, restrictions on cash transactions are essential for strengthening transparency, improving economic justice, and supporting the purposes of Sharia (maqāṣidal-syarīah) in the protection of property (ḥifẓ al-māl). However, the implementation of this policy still faces challenges in the informal sector, among MSME entrepreneurs, and in communities that lack access to banking. This study emphasises the need for policy improvements, financial inclusion, and public education to support the effectiveness of cash transaction restrictions.